Determinants of Village Heads’ Managerial Performance: The Role of Interpersonal Communication, Personality, and Work Motivation - Tika Siti Jatnika; Anoesyirwan Moeins; Widodo Sunaryo (Yayasan Aya Sophia Indonesia, 2026)
The managerial performance of village heads plays a critical role in ensuring effective local governance, particularly in the context of decentralized public administration. However, empirical evidence indicates that village governance performance remains suboptimal, reflecting limitations in managerial capacity. This study aims to examine the influence of interpersonal communication, personality, and work motivation on the managerial performance of village heads through an integrated causal model. A quantitative approach with an explanatory survey design was employed, involving 115 village heads in Bogor Regency selected through probability sampling. Data were collected using structured questionnaires and analyzed using path analysis to assess both direct and indirect relationships among variables. The results reveal that interpersonal communication, personality, and work motivation have positive and significant effects on managerial performance, with work motivation emerging as the most dominant predictor. Interpersonal communication and personality also significantly influence work motivation; however, the mediating role of work motivation is not stronger than the direct effects. These findings indicate that managerial performance is primarily driven by internal motivational factors, supported by effective communication and adaptive personality traits. The novelty of this study lies in the development of an integrative empirical model that simultaneously examines direct and indirect relationships among behavioral variables in the context of village governance, which has been rarely explored in prior research. This study contributes to the advancement of public sector organizational behavior theory and provides evidence-based insights for improving the managerial performance of village heads.